Strain Hardening of Low-Carbon Steel in the Area of Jerky Flow - Vakulenko, I. O.; Bolotova, D. M; Proidak, S. V; Kurt, B; Erdogdu, A. E; Chaikovska, H. O; Asgarov, K (Science and Transport Progress, 2021)
Purpose. The aim of this work is to assess the effect of ferrite grain size of low-carbon steel on the development of strain hardening processes in the area of nucleation and propagation of deformation bands. Methodology. Low-carbon steels with a carbon content of 0.06–0.1% C in various structural states were used as the material for study. The sample for the study was a wire with a diameter of 1mm. The structural studies of the metal were carried out using an Epiquant light microscope. Ferrite grain size was determined using quantitative metallographic techniques. Different ferrite grain size was obtained as a result of combination of thermal and termo mechanical treatment. Vary by heating temperature and the cooling rate, using cold plastic deformation and subsequent annealing, made it possible to change the ferrite grain size at the level of two orders of magnitude. Deformation curves were obtained during stretching the samples on the Instron testing machine. Findings. Based on the analysis of stretching curves of low-carbon steels with different ferrite grain sizes, it has been established that the initiation and propagation of plastic deformation in the jerky flow area is accompanied by the development of strain hardening processes. The study of the nature of increase at dislocation density depending on ferrite grain size of low-carbon steel, starting from the moment of initiation of plastic deformation, confirmed the existence of relationship between the development of strain hardening at the area of jerky flow and the area of parabolic hardening curve. Originality. One of the reasons for decrease in Luders deformation with an increase of ferrite grain size of low-carbon steel is an increase in strain hardening indicator, which accelerates decomposition of uniform dislocations distribution in the front of deformation band. The flow stress during initiation of plastic deformation is determined by the additive contribution from the frictional stress of the crystal lattices, the state of ferrite grain boundaries, and the density of mobile dislocations. It was found that the size of dislocation cell increases in proportion to the diameter of ferrite grain, which facilitates the development of dislocation annihilation during plastic deformation. Practical value. Explanation of qualitative dependence of the influence of ferrite grain size of a low-carbon steel on the strain hardening degree and the magnitude of Luders deformation will make it possible to determine the optimal structural state of steels subjected to cold plastic deformation.